The Association Between Periodontitis and Cardiovascular Disease: Clinical Implications for Treatment and Prevention - Julia Krasnoborska; Katarzyna Szmyt; Sylwia Samojedny; Katarzyna Szymańska; Kamil Walczak; Klaudia Wilk-Trytko; Maciej Superson; Juia Zarębska (Quality in Sport, 2024)
Introduction and purpose: Chronic inflammation in the oral cavity poses significant risks to both the heart and the circulatory system. A growing number of studies indicate a correlation between periodontal health and the likelihood of developing cardiovascular conditions, including myocardial infarction, coronary artery disease, hypertension, and stroke. This review aims to summarize recent reports, define current state of knowledge, and propose optimal treatment and prevention strategies.